Food wastes and By-products nutraceutical and health potential - Campos Vega, Rocío; Vergara-Castañeda, Haydé Azeneth; Oomah, B. D. (B. Dave) (Wiley Blackwell, 2020)
"An in-depth review of the innovative methods and technologies for reducing food waste and increasing the health-enhancing benefits of reconstituted by-products The environmental and economic impacts of food wastage are of increasing concern in the functional food sector--approximately a third of cereals and nearly half of fruits and vegetables go to waste worldwide. Food Wastes and By-products is a comprehensive survey of food wastage, covering the physical properties, supply, processing, and potential health benefits of recovered food waste and its reconstituted by-products. Written by leading researchers in the field, this innovative text focuses on the nutraceutical factors and bioactive compounds found within fruit, vegetable, and cereal waste. The text provides essential information on the supply of waste and its composition, identifies foods rich in valuable bioactive compounds, and explores innovative methods and technologies for the extraction and processing of high-value by-products from fruit, vegetable, and seed waste. The authors discuss the nutraceutical properties of value-added by-products and their uses in the manufacturing of dietary fibers, food flavors, supplements, pectin, and others"--